Social work practice with survivors of sex trafficking and commercial sexual exploitation - Nichols, Andrea J.; Edmond, Tonya; Heil, Erin C. (Columbia University Press, 2018)
"As awareness and identification of sex trafficking and exploitation have grown, so has the need for improved social work responses. In this volume, expert practitioners, survivors, and researchers model the best practices for working with this population, using case examples and illustrative guides. Chapters cover the common challenges of working with trafficked and exploited people and how to overcome them, including topics like runaway youth, trauma-bonds, system-level challenges, and resource scarcity. Intended as a teaching tool for students or a supplementary manual for organizations, this book emphasizes interventions and treatments, working with specific populations, programmatic design recommendations, preventative work, and outreach interventions. Researchers, students, and practitioners will find a comprehensive guide to the emerging field of practice with sex trafficking and exploitation survivors."--Publisher description.